A Combined Magnetic‐Acoustic Device for Simultaneous, Coaligned Application of Magnetic and Ultrasonic Fields. Issue 7 (11th June 2018) - Barnsley, Lester C.; Gray, Michael D.; Beguin, Estelle; Carugo, Dario; Stride, Eleanor
Abstract: Acoustically‐responsive microbubbles have been widely researched as agents for both diagnostic and therapeutic applications of ultrasound. There has also been considerable interest in magnetically‐functionalised microbubbles as multi‐modality imaging agents and carriers for targeted drug delivery. In this paper, we present a design for an integrated device capable of generating co‐aligned magnetic and acoustic fields in order to accumulate microbubbles at a specific location and to activate them acoustically. For this proof‐of‐concept study, the device was designed to concentrate microbubbles at a distance of 10 mm from the probe's surface, commensurate with relevant tissue depths in preclinical small animal models. Previous studies have indicated that both microbubble concentration and duration of cavitation activity are positively correlated with therapeutic effect. The utility of the device was assessed in vitro tests in a tissue‐mimicking phantom containing a single vessel (1.2 mm diameter). At a peak fluid velocity of 4.2 mm s−1 microbubble accumulation was observed under B‐mode ultrasound imaging and the corresponding cavitation activity was sustained for a period more than 4 times longer than that achieved with an identical acoustic field but in the absence of a magnet. The feasibility of developing a larger scale device for human applications is discussed. Abstract : Drug‐loaded microbubbles have shown considerable potential as stimuli‐responsive agents for therapeutic delivery. Incorporating magnetic nanoparticles into the bubble coating enables them to be concentrated at a target site. This paper presents a device for simultaneously applying magnetic and ultrasound fields at a selected tissue depth to enable concurrent microbubble targeting and activation.